Mycobacterium tuberculosis and SARS-CoV-2 Coinfections: A Review - Bostanghadiri, Narjess; Jazi, Faramarz Masjedian; Razavi, Shabnam; Fattorini, Lanfranco; Darban-Sarokhalil, Davood (Frontiers in Microbiology, 2022)
Abstract Background: Tuberculosis (TB) is still one of the most important causes of death worldwide. The lack of timely attention on TB diagnosis and treatment during the Coronavirus Disease 2019 (COVID-19) pandemic is a potential threat to health issues and may have severe consequences for patients and health systems. There is not much information on the management of TB during this period. Here, we reviewed the current literature to evaluate the rate of Mycobacterium tuberculosis and Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) co-infections and interactions between these infectious agents. Methods: Several databases, including Web of Science, Scopus, and Medline (via PubMed), were searched for original articles addressing TB and COVID-19 diseases published from December 2019 to April 2021. Results: Out of 3879 articles, Fifty-seven articles were included in this study, and among 106,033 patients affected by COVID-19, 891 also had TB. Overall, investigators found a consistent increase in C-reactive protein, D-dimer (especially in patients with severe clinical manifestation), erythrocyte sedimentation rate, lactate dehydrogenase, alanine aminotransferase, and a reduction of lymphocytes. The respiratory symptoms of TB/COVID-19 patients were similar to those of TB, but the risk of developing pulmonary TB increased in COVID-19 patients. Also, the mortality rate in TB/COVID-19 patients was higher than patients affected only by COVID-19 or TB. Conclusion: Some reports indicated worsening respiratory symptoms and even activation of latent TB after COVID-19 or vice versa. It seems that both active and previously treated TB constituted a risk factor for COVID-19 in terms of severity and mortality, regardless of other underlying diseases and patient status. Health systems should not neglect TB during this era of the ongoing COVID-19 pandemic by setting up appropriate diagnostic and clinical management algorithms.